Microbial investigation of biofilms recovered from endotracheal tubes using sonication in intensive care unit pediatric patients - Thiago de Oliveira Ferreira (Brazilian Journal of Infectious Diseases, 2016)
Objectives: To compare cultured microorganisms identified on endotracheal tubes biofilms through sonication technique with traditional tracheal aspirate collected at extubation of pediatric intensive care unit patients. Methods: Demographic and epidemiological data were analyzed to identify factors possibly related with the microbiological profile of the two collection methods. Associations between categorical and continuous variables were analyzed using the chi-square or Fisher's exact test, or Student's t test. p-Value <0.05 were considered significant. Results: Thirty endotracheal tubes and tracheal aspirates samples from 27 subjects were analyzed. Only one patient presented the clinical diagnosis of ventilator-associated pneumonia. Overall, 50% of bacteria were Gram-negative bacilli, followed by Gram-positive bacteria in 37%, and fungi in 10%. No statistically significant difference on the distribution of Gram-positive or Gram-negative bacteria (p = 0.996), and fungi (p = 0.985) were observed between the collection methods. Pseudomonas spp. was the most frequent microorganism identified (23.8%), followed by Streptococcus spp. (18.5%), Acinetobacter spp. (15.9%), coagulase-negative staphylococci (11.2%), and Klebsiella spp. (8.6%). Concordant results between methods amounted to 83.3%. Pseudomonas aeruginosa and Acinetobacter baumannii showed carbapenem resistance in 50% and 43.7% of the isolates, respectively. In general, cultures after endotracheal tubes sonication (non-centrifuged sonication fluid and centrifuged sonication fluid) yielded bacteria with higher rates of antimicrobial resistance compared to tracheal aspirates cultures. Additionally, in 12 subjects (40%), we observed discrepancies regarding microbiologic profiles of cultures performed using the collection methods. Conclusions: Our study demonstrated that sonication technique can be applied to ET biofilms to identify microorganisms attached to their surface with a great variety of species identified. However, we did not find significant differences in comparison with the traditional tracheal aspirate culture approach. Keywords: Sonication, Endotracheal tube, Biofilm, Tracheal aspirate